The Expression of Social and Emotional Competencies of Leadership in Lithuanian Organizations: The Gender Approach - Šilingienė, Violeta; Stukaitė, Dalia (Information & Media, 2019)
The phenomenon of gender leadership is a controversial object in contemporary leadership studies. These days, the possibilities of traditional leadership have been limited by the ongoing dynamic, global changes, which have influenced the emergence of female leadership as an independent phenomenon and its separation from the male leadership. Presently, possibilities exist to form new insights about gender leadership. Scholars have begun an intense scientific discussion on the advantages and disadvantages of male and female leadership. The goal of this paper is to disclose the social and emotional leadership competencies of different gender employees. The employed research methods are as follows: an analysis and synthesis of scientific literature with the aim of revealing the peculiarities of gender leadership and defining leadership as a set of social and emotional competencies; quantitative research conducted using a questionnaire-based survey with the aim of empirically determining the manifestation of social and emotional leadership competencies in terms of gender leadership. The theoretical analysis allows us to identify the fundamental trends of gender leadership research. The empirical basis of this article comprises the results of empirical research carried out in 2018. The paper includes an abstract of the theoretical research of gender leadership and the social and emotional leadership competencies based on the research methodology and the results received. According to the results of the empirical research, it is possible to find matching assessments of social and emotional leadership competencies in men and women; certain significant differences exist as well. These results revealed which of the advantages possessed by female leaders tend to lie in their soft management skills: interaction, trust, as well as relationships and skills in working with people.